Hubungan Antara Dukungan Sosial Dengan Motivasi Hidup Pada Penderita Thalassemia Mayor Di Rsud Dr. Moewardi Surakarta - Santoso, Frendi, Dra. Partini, M.Si. Psi (2017)
The aim of this research is for testing relation between social support to the motivation of thalassemia major. The first supposition in this research is there are a positive relation between social support to the motivation of thalassemia major. the higher of social support will make a higher motivation for thalassemia major and otherwise the low of social support will make a low motivation of thalassemia major. Subject in this research is patient of thalassemia major that undergoing medication in RSUD Dr. Moewardi Surakarta aged 5-15 years old. The sampling technique used is purposive non random sampling. That based on specific characteristics. Using scale of social support and motivation of life. Data analysis technique used is Correlation product moment Pearson technique to examine the relationship between social support and motivation of life in patients with thalassemia major. Correlation product moment Pearson indicate coefficient of rxy = 0,673 with p = 0,000 (p < 0,01) that meant there are relation more significant between social support to the motivation of thalassemia major in RSUD Dr. Moewardi Surakarta. The research hypothesis is accepted. Coefficient determinant (r2) is 0,673 so contribution social support of life motivation is 45,3%. Level of social support of thalassemia major is high with the average empirical (RE) is = 79,91 and average hypothetical (RH) is 65 in the range 72,8 ≤ x< 84,4. Then variable motivation has average empirical (RE) is 60,20 and average hypothetical ( RH) is 52,5 in the range 58,8 ≤ x< 71,4 that motivation of thalassemia major is high. Keyword: Social support, Motivation, Thalasemia major